Cardiac complications in a metamizole-induced type I Kounis syndrome - Juste,Jose F. Martínez (2016)
ABSTRACT Kounis syndrome is defined as the coincidental occurrence of allergic reaction and acute coronary syndrome secondary to vasospasm. Anti-inflammatory drugs are included as one of the multiple causes. Current data available about this syndrome come from case reports. We present the case of a patient who suffered Kounis syndrome with cardiogenic shock and asystole after intravenous infusion of Metamizole, and in which no lesions were observed in coronariography.